Unusual Reactions to Hymenoptera Stings: Current Knowledge and Unmet Needs in the Pediatric Population - Castagnoli, Riccardo; Giovannini, Mattia; Mori, Francesca; Barni, Simona; Pecoraro, Luca; Arasi, Stefania; Saretta, Francesca; Mastrorilli, Carla; Liotti, Lucia; Caminiti, Lucia; Sturm, Gunter Johannes; Marseglia, Gian Luigi; et al. (Frontiers in Medicine, 2021)
Hymenoptera stings are generally well tolerated and usually cause limited local reactions, characterized by self-resolving erythema and edema associated with pain. However, Hymenoptera stings can induce immediate and delayed hypersensitivity reactions. In addition to these manifestations, unusual reactions to Hymenoptera stings have been reported. The latter are defined as unusual because of their atypical characteristics. They may differ from hypersensitivity reactions due to the stings' particular localization and the unusual involvement of one or more specific organs. Although unusual reactions to Hymenoptera stings are infrequent, it is essential for clinicians to know the possible related clinical manifestations. Here, we review the available literature and propose a diagnostic and management algorithm. Further studies are needed to better define these conditions and the underlying pathogenetic mechanisms to improve the diagnostic and therapeutic approach.